Comparative study of vapor pressure requirements for rule-based design of IMO Type C tanks for LCO2: Guidelines for optimizing pressure conditions - Younseok Choi; Jinkwang Lee; Jae Min Lee (International Journal of Naval Architecture and Ocean Engineering, 2025)
The safe and efficient design of liquefied carbon dioxide (LCO2) storage tanks is essential for carbon capture, utilization, and storage (CCUS), particularly in maritime transport. IMO Type C pressure vessels are widely used, with minimum design vapor pressure determined by rule-based criteria. These regulations, based on fracture mechanics principles, prevent crack propagation-induced leaks. However, discrepancies between regulatory and operational pressures increase design complexity and iterative modifications. This study presents a thermodynamic framework to assess the gap between rule-based and actual vapor pressures and identifies volume-dependent implications for pressure control and insulation design. Simulations for 1000–5000 m3 tanks show that small tanks (1000–2000 m3) may exceed regulatory pressure limits, requiring enhanced insulation or pressure control. In contrast, large tanks (3000–5000 m3) are governed by conservative rule-based limits, suggesting potential for operational adjustments. The results offer an early-stage design guide balancing efficiency and regulatory compliance, supporting safe, economical marine LCO2 transport system development.